The Relationship and Benefits of Aligning Communication Management and Information System Management : Case: Tietokeskus Oy - Ruuhijärvi, Tuomas (My University, 2023)
Internal communication management has been rising in popularity in the communication management domain in recent years. Organizations have started seeing employees as one of the most important stakeholders to communicate effectively. In the modern business landscape, most managers find themselves conducting internal communications through some kind of communication technology, and in most cases through many at the same time. Virtual teams are becoming commonplace in organizations and have created the need for channels and networks through which communications can be done fast and easily. Even if virtual teams are not used, communication technology usage for internal communications brings many benefits. The goals of this research are to identify the relationship between communication management and information system management practices and to identify the drivers of internal communication success and use them in creating an effective internal communication strategy. Qualitative case study research was conducted using the Gioia-method. The research data for this thesis was gathered by conducting semi-structured interviews within the case organization. Ten interviews were conducted with participants from every business unit within the case organization to obtain as much diversity of answers as possible. These interviews helped in understanding what are the drivers of effective internal communications and what are the allignment points between communication management and information system management. Additionally, a questionaire was held within the case organization, which helped in understanding the case organization’s internal communication satisfaction. In addition a literature review was gathered from the subjects of communication management and information system management. From the communication management literature, an internal communication matrix was selected as the theoretical backbone for understanding organizations’ internal communication aspects. Furthermore, from information system management literature, information technology system management is used as the framework for how the management of organizations’ IT systems is conducted. The found research results were shown in two distinct data structures about: the key alignment points between communication management and information system management as well as the drivers of effective internal communication strategy. These data structures were created by first open-coding the gathered interview data to create 1st-order codes. From these codes 2nd-order categories were created, and ultimately three aggregate dimensions for both data structures were found. The research found alignment points between communication management and information system management, which were: enhanced communication, change management, and crisis management. Furthermore, an internal communication strategy framework is created through which organizations can create a more effective internal communication strategy.

Sisäisen viestinnän hallinta on viime vuosina kasvattanut suosiotaan viestinnän hallinnan alalla. Organisaatiot ovat alkaneet pitää työntekijöitä yhtenä tärkeimmistä sidosryhmistä, joille on viestittävä tehokkaasti. Nykyaikaisessa yritysmaailmassa useimmat johtajat toteuttavat sisäistä viestintää jonkin viestintäteknologian avulla, ja useimmiten useiden eri viestintäteknologioiden avulla samanaikaisesti. Virtuaalitiimit ovat yleistymässä organisaatioissa, ja ne ovat luoneet tarpeen kanaville ja verkostoille, joiden kautta viestintä voidaan hoitaa nopeasti ja helposti. Vaikka virtuaalitiimejä ei käytettäisikään, viestintäteknologian käyttö sisäisessä viestinnässä tuo monia etuja. Tämän tutkimuksen tavoitteina on selvittää viestinnän hallinnan ja tietojärjestelmien hallinta käytäntöjen välinen suhde sekä tunnistaa sisäisen viestinnän onnistumisen ajurit ja käyttää niitä tehokkaan sisäisen viestintästrategian luomisessa. Laadullinen case-tutkimus toteutettiin Gioia-menetelmää käyttäen. Tämän tutkielman tutkimusaineisto kerättiin tekemällä puolistrukturoituja haastatteluja case-organisaatiossa. Kymmenen haastattelua suoritettiin, ja osallistujia oli kaikista case-organisaation liiketoimintayksiköistä, jotta saataisiin mahdollisimman monipuolisia vastauksia. Haastattelut auttoivat ymmärtämään, mitkä ovat tehokkaan sisäisen viestinnän taustatekijät ja mitkä ovat kommunikaation hallinnan ja tietojärjestelmien hallinnan liittymäkohdat. Lisäksi case-organisaatiossa järjestettiin kysely, joka auttoi ymmärtämään case-organisaation sisäisen viestinnän tyytyväisyyttä. Lisäksi kerättiin kirjallisuuskatsaus kommunikaatio hallinnan ja tietojärjestelmien hallinnan aiheista. Kommunikaatio hallinnan koskevasta kirjallisuudesta valittiin sisäisen viestinnän matriisi teoreettiseksi selkärangaksi organisaatioiden sisäisen kommunikaation näkökohtien ymmärtämiseksi. Lisäksi tietojärjestelmien hallintaa käsittelevästä kirjallisuudesta käytetään information technology system management:ia viitekehyksenä sille, miten organisaatioiden tietoteknisten järjestelmien hallintaa toteutetaan. Löydetyt tutkimustulokset esiteltiin kahdessa eri rakennemallissa, jotka koskivat seuraavia asioita: viestinnän johtamisen ja tietojärjestelmien johtamisen väliset keskeiset yhteensovittamispisteet sekä tehokkaan sisäisen kommunikaatiostrategian ajurit. Nämä tietorakenteet luotiin avoimesti koodaamalla kerätty haastatteluaineisto ensin 1. asteen käsitteiden luomiseksi. Näistä käsitteistä luotiin 2. asteen teemat, ja lopulta molemmille tietorakenteille löydettiin kolme kokonaisdimensiota. Tutkimuksessa löydettiin kommunikaatio hallinnan ja tietojärjestelmien hallinnan välisiä yhtymäkohtia, jotka olivat: tehostettu viestintä, muutos hallinta ja kriisinhallinta. Lisäksi voitiin luoda sisäisen kommunikaation strategian viitekehys, jonka avulla organisaatiot voivat luoda tehokkaamman sisäisen kommunikaatiostrategian.
Keywords: Communication management, Information system management, Internal communication strategy